2010
DOI: 10.1007/s11661-010-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Interfaces on Hardness and Thermal Stability of Nanocrystalline Ti0.5Al0.5N Coatings

Abstract: The effect of microstructure on the thermal stability and hardness of the cathodic arc evaporated Ti 0.5 Al 0.5 N coatings was investigated with the aid of the in-situ high-temperature X-ray diffraction experiments, which were accompanied by high-resolution transmission electron microscopy (HRTEM) and nanoindentation measurements. The microstructure of the coatings was modified through the choice of the bias voltage in the deposition process. It was found that the bias voltage affects strongly the uniformity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…This slope, is governed by segregations and also influenced by dislocations which was also observed for other systems that obey Vegard's rule of mixture [28][29][30]. Since, thanks to the EDX measurements, the effect of the lattice parameter variation can be separated from the microstrain.…”
Section: Icp-oes Edx Grain Interior Grain Boundarysupporting
confidence: 60%
“…This slope, is governed by segregations and also influenced by dislocations which was also observed for other systems that obey Vegard's rule of mixture [28][29][30]. Since, thanks to the EDX measurements, the effect of the lattice parameter variation can be separated from the microstrain.…”
Section: Icp-oes Edx Grain Interior Grain Boundarysupporting
confidence: 60%
“…9. Formation of tensile strains during decomposition has also been observed experimentally for Ti 0.50 Al 0.50 N thin films [27]. As was discussed in the previous section, the decomposition is expected to begin already before 950 °C for [35] observed that for a two-phase mixture of hexagonal and cubic phases in high Al content TiAlN the lattice strains were increased compared to a single phase film.…”
supporting
confidence: 63%
“…The presence of two or more phases can result in epitaxial misfit strains [25]. Further, phase transformations in the film after growth can cause additional strains [18,26,27].…”
Section: Structure and Strain Of As-deposited Filmsmentioning
confidence: 99%
“…The archetype for this approach is the metastable cubic (c-) Ti 1-x Al x N solid solution, which forms nm-sized domains by spinodal decomposition when exposed to high temperatures (around 900 °C) [5][6][7][8]. At even higher temperatures this alloy further decomposes into its thermodynamically stable phases c-TiN and wurtzite (w-) AlN [9] that deteriorates the mechanical properties [10,11]. The related Zr 1-x Al x N alloys display characteristics similar to Ti 1-x Al x N with a miscibility gap for cubic solid solutions and a higher driving force for decomposition compared to Ti 1-x Al x N [12,13] resulting in promising mechanical properties [14][15][16][17][18] at high temperature.…”
Section: Introductionmentioning
confidence: 99%